Application of science and technology to increase the small production capacity of cake market products - Dewi, Elita; Berlianti (Talenta Publisher, 2019)
One of the many developing UMKM today is the snack business. Snack business is a household-scale business that has very good opportunities for now and in the future. Market demand for snacks continues to flow. Seeing snack lovers, not only children, but also teenagers, adults, to the elderly. So it is not surprising that the food business that is often served as a distraction while doing this activity is often flooded with customers. Making this snack business opportunity becomes more wide open. The low production capacity that is owned makes this business less developed. Besides that the equipment used is also simple and is still traditional in nature, so it takes a long time and is very draining. For this reason, science and technology is needed that will make the production process easier and cheaper. In connection with this, it is felt necessary to provide assistance and training to improve the capacity of community service partners. Besides improving the marketing strategy so that it has the ability to market the market snacks in production, so as to create and have a lot of marketing networks. Training is needed to enable entrepreneurs to calculate total sales revenue and total costs so that they are able to know how much profit is earned per unit of production. It is expected that after the mentoring, the partners will become more knowledgeable, able to apply this knowledge in their daily work and transmit this knowledge to other entrepreneurs.